Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1038/349790a0
|View full text |Cite
|
Sign up to set email alerts
|

Odorant signal termination by olfactory UDP glucuronosyl transferase

Abstract: The onset of olfactory transduction has been extensively studied, but considerably less is known about the molecular basis of olfactory signal termination. It has been suggested that the highly active cytochrome P450 monooxygenases of olfactory neuroepithelium are termination enzymes, a notion supported by the identification and molecular cloning of olfactory-specific cytochrome P450s (refs. 13-16). But as reactions catalysed by cytochrome P450 (refs 17, 18) often do not significantly alter volatility, lipophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(127 citation statements)
references
References 34 publications
7
117
0
2
Order By: Relevance
“…Ugt2a1 and Ugt2a2 are expressed in the nasal epithelium, and studies using recombinant enzymes have shown that they are able to conjugate odorants. This is hypothesized to be important in the termination of odorant signaling and preventing receptor desensitization (Lazard et al, 1991;Sneitz et al, 2009). The DUgt2 mouse line should allow this hypothesis to be tested, both in vitro using cultured nasal epithelial cells and in vivo using odordependent behavioral paradigms (Friedrich, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ugt2a1 and Ugt2a2 are expressed in the nasal epithelium, and studies using recombinant enzymes have shown that they are able to conjugate odorants. This is hypothesized to be important in the termination of odorant signaling and preventing receptor desensitization (Lazard et al, 1991;Sneitz et al, 2009). The DUgt2 mouse line should allow this hypothesis to be tested, both in vitro using cultured nasal epithelial cells and in vivo using odordependent behavioral paradigms (Friedrich, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The liver is a major site of glucuronidation as evidenced by the quantitative analysis. However, extrahepatic glucuronidation is also known to occur in organs such as the lung, kidney, gastrointestinal mucosa, prostate and olfactory epithelium [28][29][30][31][32][33]. The overall quantitative contribution of extrahepatic glucuronidation is much smaller compared with hepatic glucuronidation.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of UGT2As was proposed to be the termination of the odorant signals, although it is not limited to this function since they are expressed in the liver, small intestine, brain and fetal lung. [102][103][104] The wide range of substrates for human UGTs includes compounds of diverse chemical structures. Several studies have described the overlapping substrate specificities of UGT proteins.…”
Section: A Brief Overview Of the Glucuronidation Pathway And Human Ugtsmentioning
confidence: 99%